Prescriber and Patient Responsibilities in Treatment of Acute Respiratory Tract Infections — Essential for Conservation of Antibiotics - Antonio C. Pignatari; Aurelio Sessa; Roman Kozlov; Attila Altiner; John S. Oxford; John Bell; Martin G. Duerden; Alike van der Velden; Sabiha Y. Essack (Antibiotics, 2013)
Inappropriate antibiotic use in normally self-limiting acute respiratory tract infections (RTIs), such as sore throat and the common cold, is a global problem and an important factor for increasing levels of antibiotic resistance. A new group of international experts—the Global Respiratory Infection Partnership (GRIP)—is committed to addressing this issue, with the interface between primary care practitioners and their patients as their core focus. To combat the overuse of antibiotics in the community, and facilitate a change from prescribing empiric antibiotic treatment towards cautious deferment combined with symptomatic relief, there is a need to introduce and enhance evidence-based dialogue between primary care practitioners and their patients. Communication with patients should focus on the de-medicalisation of self-limiting viral infections, which can be achieved via a coherent globally endorsed framework outlining the rationale for appropriate antibiotic use in acute RTIs in the context of antibiotic stewardship and conservancy. The planned framework is intended to be adaptable at a country level to reflect local behaviours, cultures and healthcare systems, and has the potential to serve as a model for change in other therapeutic areas.